Antiviral activity of baicalein and quercetin against the Japanese encephalitis virus - Johari, Jefree; Kianmehr, Aynaz; Mustafa, Mohd Rais; AbuBakar, Sazaly; Zandi, Keivan (MDPI, 2012)
Japanese encephalitis (JE), a mosquito-borne viral disease, is endemic to the entire east and southeast Asia, and some other parts of the world. Currently, there is no effective therapeutic available for JE; therefore, finding the effective antiviral agent against JEV replication is crucial. In the present study, the in vitro antiviral activity of baicalein and quercetin, two purportedly antiviral bioflavonoids, was evaluated against Japanese encephalitis virus (JEV) replication in Vero cells. Anti-JEV activities of these compounds were examined on different stages of JEV replication cycle. The effects of the compounds on virus replication were determined by foci forming unit reduction assay (FFURA) and quantitative RT-PCR. Baicalein showed potent antiviral activity with IC50 = 14.28 µg/mL when it was introduced to the Vero cells after adsorption of JEV. Quercetin exhibited weak anti-JEV effects with IC50 = 212.1 µg/mL when the JEV infected cells were treated with the compound after virus adsorption. However, baicalein exhibited significant effect against JEV adsorption with IC50 = 7.27 µg/mL while quercetin did not show any anti-adsorption activity. Baicalein also exhibited direct extracellular virucidal activity on JEV with IC50 = 3.44 µg/mL. However, results of quantitative RT-PCR experiments confirmed the findings from FFURA. This study demonstrated that baicalein should be considered as an appropriate candidate for further investigations, such as the study of molecular and cellular mechanism(s) of action and in vivo evaluation for the development of an effective antiviral compound against Japanese encephalitis virus.